Effect of various stitching patterns on mechanical properties of jute fiber reinforced composite. (2023) - Gukendran, R.; Sambathkumar, M.; Prakash Raj, T.; Nalinkumar, S.; Nivaas, B.; Sai Pranesh Kumar, B.
Abstract: Natural fiber composites are found as an interesting alternative material for eco-friendly and cost-effectiveness in comparison to synthetic composites. However, natural fiber composite shows poor interfacial strength and mechanical properties at critical situations due to its weak fiber orientation and weak bonding at the fiber–matrix interface. This study investigates the mechanical behaviour of stitched jute fiber reinforced composite matrix. The composite was made by hand layup method with 40% of jute fiber into epoxy matrix. The jute fibers are stitched by various stitching patterns like square, tilt 45/45, double column stitch and dense rectangular stitch. The assembly of the jute fiber mat is stitched using nylon thread for better control in orientation during the test sample preparation. The test samples prepared from the different stitched composites are tested for its tensile, flexural and impact strength using a standard universal tensile testing machine. The results show that the double column stitch composite matrix attained a maximum strength against all mechanical behaviour tests.